DEVELOPING AN ENTREPRENEURSHIP LEARNING BOOK USING THE SOCIETY 5.0-BASED BLENDER LEARNING MODEL FOR UNIVERSITAS BINA MANDIRI GORONTALO STUDENTS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
This research delivers the final product of an entrepreneurship learning book using the society 5.0-based blended learning model for Universitas Bina Mandiri Gorontalo students. The research type was research and development using Dick and Carey’s model. Data were collected using interviews, questionnaire distribution, and observation. The approaches were qualitative, and the research type was descriptive. Research procedures were: (1) preliminary study, (2) design development, (3) expert and practitioner validation, (4) limited test, (5) model implementation, and (6) model recommendation. We then acquired the following results. The society 5.0-based entrepreneurship learning book developed in the COVID-19 era for undergraduate management students taking their semester 4 at Universitas Bina Mandiri Gorontalo using Dick and Carey’s model was considered very practical in terms of its practicality. The book was also considered effective. The same result was demonstrated by the Wilcoxon Signed Ranks Test. It was attested that the entrepreneurship learning book was effective. Lecturer and student assessment results, acquired from distributed questionnaires, exhibited high effectiveness (student assessment, 85.23%; lecturer assessment, 89.77%, on average). The results brought about a new model, i.e., the IMAM Model, referenced from two learning models, namely Dick and Carey’s and blended learning models. The IMAM model as a learning model began by identification, class management, adaptiveness and activeness, and independence, becoming the representatives of the spirit of Gorontalo local wisdom values, i.e., mooluhu, which was independence.